2000
DOI: 10.1021/jp9941918
|View full text |Cite
|
Sign up to set email alerts
|

Short and Medium Range Order in Sodium Aluminoborate Glasses. 2. Site Connectivities and Cation Distributions Studied by Rotational Echo Double Resonance NMR Spectroscopy

Abstract: A quantitative NMR strategy is developed for the study of the network connectivity (intermediate range structure) and the cation distribution in the sodium aluminoborate glass system. The strategy is based on the analysis of rotational echo double resonance (REDOR) spectroscopy applied to the glasses and the crystalline model compounds Li 6 Al 2 (BO 3 ) 4 , NaBO 2 , and Na 2 B 4 O 7 . The heterodipolar multispin interaction between the quadrupolar spin systems 27 Al T 11 B and 23 Na T 11 B is analyzed in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
176
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 120 publications
(191 citation statements)
references
References 29 publications
12
176
3
Order By: Relevance
“…Similar preferences for heteroatomic linkages were detected by comprehensive spectroscopic studies of the sodium and silver borophosphate glass system along other composition lines [27,[79][80][81][82], in sodium aluminophosphate glasses [83] and in sodium aluminoborate glasses [84][85][86]. In contrast, preferences for homo-atomic connectivities were detected by dipolar NMR spectroscopic methods in borosilicate [87] 3 , and TeO 2 can be incorporated into glassy NaPO 3 , over wide composition ranges, producing strong effects on their physical properties.…”
Section: P and B (4)supporting
confidence: 62%
“…Similar preferences for heteroatomic linkages were detected by comprehensive spectroscopic studies of the sodium and silver borophosphate glass system along other composition lines [27,[79][80][81][82], in sodium aluminophosphate glasses [83] and in sodium aluminoborate glasses [84][85][86]. In contrast, preferences for homo-atomic connectivities were detected by dipolar NMR spectroscopic methods in borosilicate [87] 3 , and TeO 2 can be incorporated into glassy NaPO 3 , over wide composition ranges, producing strong effects on their physical properties.…”
Section: P and B (4)supporting
confidence: 62%
“…Most recently, we have shown that also for multiple-spin systems involving quadrupolar nuclei the initial parts of RE-DOR curves (data range 0 Յ ⌬S/S 0 Յ 0.3) can be conveniently analyzed in terms of van Vleck's second moment information, even if the order and geometry of the spin system is completely unknown (14). In practice, however, the significance of any REDOR analysis largely depends on the fidelity of the experimental REDOR curves.…”
Section: Introductionmentioning
confidence: 99%
“…4. As previously discussed, REDOR data in multispin systems can be analyzed with the parabolic approximation [39] applied to the short-term evolution behavior (0 rDS/S o r0.2) using the expression [18,19,40]:…”
Section: B{ 27 Al} and 27 Al{ 11 B}redor Experimentsmentioning
confidence: 99%
“…For quadrupolar nuclei, the analysis is more complicated; however, as owing to the anisotropic quadrupolar interactions the p pulses applied to the non-observed I spins that are present in the non-central Zeeman states may provide less dipolar recoupling than theoretically expected or even none at all, requiring careful calibration procedures on crystalline model compounds with well-characterized spin dynamics [18,19,40]. To this end, the theoretical second moments and those obtained 100 δ ( 27 Al) / ppm Al 5 BO 9 50 0 -50 Fig.…”
Section: B{ 27 Al} and 27 Al{ 11 B}redor Experimentsmentioning
confidence: 99%
See 1 more Smart Citation